Biochemical and Hematological Profiles of Common Carp (Cyprinus Carpio) under Sublethal Effects of Trivalent Chromium - Zeynab Abedi (Iranian Journal of Toxicology, 2016)
Background: In natural waters and/or aquaculture facilities, fish are often exposed to chromium waste and demonstrate cumulative deleterious effects. To our knowledge, there are no studies concerning the effects of trivalent Cr on C. carpio hematology. This study presents hematological and some biochemical parameters of common carp, Cyprinus carpio, affected by sublethal concentration of trivalent chromium. Methods: The fish in the experimental aquaria (three replicates each) were exposed to a sublethal chromium chloride concentration of 2 mg L−1, which was prepared as stock solution and added depending on the volume of the aquaria to obtain the required concentration. After a period of 28 days, parameters such as hematocrit (Hct), hemoglobin (Hb), lymphocytes (Lym), neutrophils (Neu), total protein (TP), albumin, immunoglobulin M (IgM), glucose, red and white blood cells (RBC and WBC), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC) were examined. Results: Chromium exposure for 28 days significantly (P<0.05) reduced the amounts of Hct, Hb, RBC, WBC, MCH, and MCHC, whereas albumin and glucose significantly (P<0.05) increased in the examined fish as opposed to the control. The levels of Lym, Neu, MCV, IgM, and TP were not significantly different (P>0.05) between the Cr-exposed fish and the control. Conclusion: Hematological indices of fish, caused by chromium toxicity to C. carpio, can be secondary responses to toxicants, including exposure to low concentrations of heavy metals, which reflect the launch of stress reaction in the affected fish.